Should a Sentinel Node Biopsy Be Performed in Patients with High-Risk Breast Cancer? - Kenneth D. Westover; M. Brandon Westover; Eric P. Winer; Andrea L. Richardson; J. Dirk Iglehart; Rinaa S. Punglia (International Journal of Breast Cancer)
A negative sentinel lymph node (SLN) biopsy spares many breast cancer patients the complications associated with lymph node irradiation or additional surgery. However, patients at high risk for nodal involvement based on clinical characteristics may remain at unacceptably high risk of axillary disease even after a negative SLN biopsy result. A Bayesian nomogram was designed to combine the probability of axillary disease prior to nodal biopsy with customized test characteristics for an SLN biopsy and provides the probability of axillary disease despite a negative SLN biopsy. Users may individualize the sensitivity of an SLN biopsy based on factors known to modify the sensitivity of the procedure. This tool may be useful in identifying patients who should have expanded upfront exploration of the axilla or comprehensive axillary irradiation.